Avance de la intrusión del agua salina en el subsuelo de la parte baja de la cuenca del rio Santa Rosa en la provincia de El Oro - Román León, Cristhian Jhon (2008)
The present study on the progressive intrusión of salty water underground the low part of the Zarumilla River basin in El Oro province, had three main goals: 1.- Determine the area on which salty water is present in the underground basin of the Zarumilla River, on the Ecuadorian province of El Oro. 2.- Analyze the quality of the water used to irrigate the lands in Huaquillas and Arenillas, in El Oro. 3.- Establish an Isosalinity curve for each one of the studied to areas. Samples of water were taken alongsidethe Zarumilla River basin, from the Huaquillas shore line up to Arenillas; using a GPS it was posible to locate each one of the wells; a depth measurer enabled us to get a sample of underground water. Being 17 the wells studied to determine the salty water intrusión, it was necessary to study mixed waters and the relationship between chloride and baking soda: to achieve the second goal were evaluated the results obtained from the water analysis, applying the FAO directions. The third goal could be achieved through the Surfer program to build the maps of each of the topics we have studied. It is determined that the water has a high content of salt in all the samples, and is classified as an average quality water with increasing problems, and contamination of salty water in the 4, 5 and 7 wells, being this a serious problem since this Hill affect the water supply of the area in the coming years.